Dynamics of Drivers of Conflict in Water-Related Resource Scarcity: Focus on Lake Turkana Basin of Kenya - David Njagi Ngonge; Kariuki Muigua; Elvin Nyukuri (Eastern African Journal of Humanities and Social Sciences)
Lake Turkana basin, located in Turkana County of Kenya, has become a central point for studying the dynamics of conflicts resulting from water-related resource scarcity. The study sought to identify specific drivers of water use-related resource conflicts in the basin and was anchored on the Negotiation Theory. Historically, the semi-arid and arid regions of the Kenyan borders have experienced perennial conflicts between ethnic groups in the Lake Turkana Basin that revolve around scarce water-related resources on land and in water.  Using a descriptive study design, convenience sampling accessed 36 respondents through 36 questionnaires, interview schedules, three focus group discussions (FGDs), and an observation guide.  The study findings demonstrate that drivers of conflicts were not just locally domesticated but also had external factors and influences, including dynamics associated with inflammatory political speeches and economic and environmental factors resulting in a harsh climate. Additionally, high illiteracy, with over 45% having only primary school level education, cultural pressures where 75% male domination was observed, ethnic tensions, historical grievances, scarce critical resources which were only concentrated in a few locations, and geopolitical interests of neighbouring countries contributed to conflicts in the region. In conclusion, drivers of conflict must be carefully understood for long-term resolutions. The study limitations included remoteness and lack of infrastructure in the basin. Further research is recommended to establish whether the key drivers could be reversed in their efforts to drive conflicts to manage perennial conflicts.  Alternative Dispute Resolution (ADR) mechanisms are highly recommended for managing these perennial water resource-related conflicts.